2016
DOI: 10.3847/0004-637x/824/1/8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Radiation Cooling and Heating Function on Standing Longitudinal Oscillations in Coronal Loops

Abstract: Standing long-period (with the periods longer than several minutes) oscillations in large hot (with the temperature higher than 3 MK) coronal loops have been observed as the quasi-periodic modulation of the EUV and microwave intensity emission and the Doppler shift of coronal emission lines, and have been interpreted as standing slow magnetoacoustic (longitudinal) oscillations. Quasi-periodic pulsations of shorter periods, detected in thermal and non-thermal emissions in solar flares could be produced by a sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 55 publications
1
22
0
1
Order By: Relevance
“…Müller et al 2003), and non-linear thermal overstability (e.g. Kumar et al 2016). Also, a class of quasi-periodic pulsations in flaring energy releases that are caused by spontaneous repetitive magnetic reconnection ("magnetic dripping", see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Müller et al 2003), and non-linear thermal overstability (e.g. Kumar et al 2016). Also, a class of quasi-periodic pulsations in flaring energy releases that are caused by spontaneous repetitive magnetic reconnection ("magnetic dripping", see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some people suggested that such pulsations might be related to the slow-mode oscillations in large scale coronal loops (Svestka 1994), while other work suggested that the longperiod pulsations could be associated with gravitydriven solar interior modes and connected with the wave leakage of chromospheric oscillations (Yuan et al 2011). Another possible explanation of VLPs is the thermal overstability of standing slow magnetoacoustic waves in the magnetic flux loops (Kumar, Nakariakov, and Moon 2016), such as the SUMER oscillations with periods in the range of 5 -40 min and detected in long loops with lengths of 200 -300 Mm (Wang 2011).…”
Section: Generation Mechanism Of Preflare-vlpmentioning
confidence: 99%
“…However, the damping caused by this term is independent of k. In the case R > 0, this term suppresses damping, and can even lead to the increase in the wave amplitude, the phenomenon known as thermal overstability (e.g. see Nakariakov et al 2000a;Kumar et al 2016, for this effect on magnetoacoustic waves). The critical value of R that separates the damping and over-stable regimes is…”
Section: Linear Dispersion Relationmentioning
confidence: 99%
“…In the following we omit this subscript for the variables u and v. Following the procedure described in Afanasyev & Nakariakov (2015b) and Kumar et al (2016), we substitute expansion (7) in Eqs. (1-6) and, taking into account quadratically nonlinear terms everywhere except the terms on the right hand sides of Eqs.…”
Section: Dynamics Of Small Perturbationsmentioning
confidence: 99%
See 1 more Smart Citation